Gene expression in Leishmania: analysis of essential 5' DNA sequences. - Curotto de Lafaille, M A (1992)
A major unanswered question in Kinetoplastida parasites is the mechanism of regulating gene expression. Using a transfection system, we have previously shown that the intergenic region of the alpha-tubulin gene of Leishmania enriettii contained sequences required for gene expression. The goal of the work reported here was to determine whether the Leishmania-derived sequences were providing transcriptional control signals or functioning at a post-transcriptional level, most likely in trans-splicing. The chloramphenicol acetyltransferase (cat) gene was used as the reporter gene and was stably introduced into L. enriettii as part of an extrachromosomal element by transfection. We show here that the production of cat mRNA was dramatically dependent on the presence of the intergenic region 5' to the cat gene. The intergenic region could be substituted by a smaller fragment (222 base pairs) that contained the trans-splice acceptor site and an adjacent polypyrimidine tract. This native fragment could be replaced by a synthetic polypyrimidine tract containing an AG site. The native and the synthetic fragments had unidirectional activity. No effect on transcription of the cat gene by the wild-type fragment or the synthetic polypyrimidine was detected. The results indicate that both regions contain signals that affect RNA stability, probably sequences involved in trans-splicing.